2018
DOI: 10.1111/tran.12259
|View full text |Cite
|
Sign up to set email alerts
|

The post‐politics of plant biosecurity: The British Government's response to ash dieback in 2012

Abstract: This paper analyses the post-political nature of the discourse of plant biosecurity in the context of the response to ash dieback in Britain. Ash dieback or Chalara is a tree disease usually fatal to ash trees. It is caused by a fungal pathogen from Asia and was first discovered in Britain in 2012 at a nursery in Buckinghamshire, England, where it had arrived in a consignment of infected tree saplings imported from the Netherlands. Global trade and the rising number of epidemics affecting plants, animals and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…Previous analyzes of the use of scientific research in biosecurity governance have shown how science is used not only to legitimize certain positions but a step further, to “depoliticize” them ( 76 , 77 ). That is, when problems are framed in overly technocratic terms, it only becomes possible to contribute to debates through technical, scientific language, and wider political and value-based questions are not openly discussed ( 76 , 78 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous analyzes of the use of scientific research in biosecurity governance have shown how science is used not only to legitimize certain positions but a step further, to “depoliticize” them ( 76 , 77 ). That is, when problems are framed in overly technocratic terms, it only becomes possible to contribute to debates through technical, scientific language, and wider political and value-based questions are not openly discussed ( 76 , 78 ).…”
Section: Discussionmentioning
confidence: 99%
“…It could be said that the legislation, bureaucracy and politics at the time did not respond in a suitable fashion to deal with the threat. Lessons have been learnt in many countries in the case of the response to ash dieback (Heuch, 2014;Tsouvalis, 2019). It is envisaged that the new EU Plant health regulation (EU 2016/2031) will allow for a more rapid response to unfamiliar or novel pest threats.…”
Section: Strengthened Biosecurity To Prevent Further Pest Threats To F Excelsiormentioning
confidence: 99%
“…This brief review is of course by no means exhaustive. Other important strands of vegetal geography, some of which shall be explored further below, include recent work on vegetal labour (Ernwein, 2020; Palmer, 2020), biosecurity (Barker, 2008; Barker and Francis, 2021; Tsouvalis, 2019) and Indigenous knowledge (Arnold et al, 2021; Peach et al, 2020; Robinson and Raven, 2017). The purpose of this section has been to draw together a literature which, as yet, lacks a coherent (sub)disciplinary identity.…”
Section: Vegetal Geographymentioning
confidence: 99%
“…This leads us to pursue lines of conversation which flow not only across species and disciplinary boundaries, but also between academic and non-academic worlds (Dyke et al, 2018). Much geographical work on plant biosecurity in particular pursues these experimental provocations, asking how we might better ‘live with’ invasive species or plant disease in practice, constructing a new politics for biosecurity which can more deftly respond to ‘life’s capacity for emergence’ (Tsouvalis, 2019, p.3, Atchison, 2015). As put by Myers (in Lomeña, 2020), if we thought like a plant, we would pay more attention to what we put in our water, air and soil.…”
Section: Plant-human Attunementsmentioning
confidence: 99%